DOM DZIECIĘCY, BIEG BARJEROWY, KULTURALNO-BYTOWE OBSŁUGIWANIE, CZYLI O FRAZEMACH W POLSKOJĘZYCZNEJ PRASIE RADZIECKIEJ (NA MATERIALE „TRYBUNY RADZIECKIEJ” Z LAT 1927-1938) - Graczykowska, Tamara (Acta Neophilologica, 2016)
This article deals with the phrasemes found in the Soviet variant of the Polish language in the years preceding World War II. Analytical material is collected from “Trybuna Radziecka”, a central Polish weekly published in Moscow in 1927–1938 and edited by Polish left-wing intelligentsia, living in the USRR as political émigrés in this period. Phrasemes are classified thematically to present the new realities of life in the Soviet Union (e.g. politics – abecadło wyborcze, services – kulturalno-bytowe obsługiwanie, education – dom dziecięcy). Almost all phrasemes are borrowings from the Russian language.